2013
DOI: 10.1016/j.repc.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

One-shot diagnostic and prognostic assessment in intermediate- to high-risk acute pulmonary embolism: The role of multidetector computed tomography

Abstract: Introduction: Contrast-enhanced multidetector computed tomography (MDCT) is useful for the diagnosis of pulmonary embolism (PE). However, current guidelines do not support its use for risk assessment in acute PE patients. Objectives: We compared the prognostic impact of MDCT-derived indices regarding mediumterm mortality in a population of intermediate-to high-risk PE patients, mostly treated by thrombolysis. Methods: Thirty-nine consecutive patients admitted to an intensive care unit with acute PE were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…The OI was reported and calculated according to the Qanadli score in all 22 studies ( Table 2). One study [21] only reported on the scoring system of Mastora, and therefore was excluded; in this study, the OI was not predictive of mortality. In six studies, the prognostic value of an OI below/above predefined cut-off values was evaluated.…”
Section: Oimentioning
confidence: 97%
“…The OI was reported and calculated according to the Qanadli score in all 22 studies ( Table 2). One study [21] only reported on the scoring system of Mastora, and therefore was excluded; in this study, the OI was not predictive of mortality. In six studies, the prognostic value of an OI below/above predefined cut-off values was evaluated.…”
Section: Oimentioning
confidence: 97%
“…All but one study reported right-to-left ventricle diameter ratio measured in transverse images [23,27,35,42,44,51]. The analysis of these studies showed a significant association between right-to-left ventricle diameter ratio and death; the OR measured by random effects model was 4.65 (95% CI 1.79-12.07; p50.002) with significant heterogeneity (I 2 51%).…”
Section: Death Within 3 Monthsmentioning
confidence: 99%
“…The authors found that the right ventricular/left ventricular ratio did have prognostic implications in this population. 72 Heinrich et al compared CT findings, including the pulmonary artery diameter and the PA:A ratio, to preoperative and postoperative hemodynamic measurements in 60 patients undergoing thrombo-endarterectomy. The pulmonary artery diameter was 3.9 ± 0.55 cm and the PA:A ratio was 1.14 ± 0.2.…”
Section: Pa:a Ratio and Outcomesmentioning
confidence: 99%